Rat thalamic neurons encode complex combinations of heading and movement directions and the trajectory route during translocation with sensory conflict - Enkhjargal, Nyamdavaa; Matsumoto, Jumpei; Chinzorig, Choijiljav; Berthoz, Alain; Ono, Taketoshi; Nishijo, Hisao (Frontiers in Behavioral Neuroscience, 2014)
It is unknown how thalamic head direction neurons extract meaningful information from multiple conflicting sensory information sources when animals run under conditions of sensory mismatch. In the present study, rats were placed on a treadmill on a stage that moved in a figure-8-shaped pathway. The anterodorsal and laterodorsal neurons were recorded under 2 conditions: 1) control sessions, in which both the stage and the treadmill moved forward, or 2) backward (mismatch) sessions, in which the stage was moved backward while the rats ran forward on the treadmill. Of the 222 thalamic neurons recorded, 55 showed differential responses to the directions to window (south) and door (north) sides, along which the animals were translocated in the long axis of the trajectory. Of these 55 direction-related neurons, 15 showed heading direction-dependent responses regardless of movement direction (forward or backward movements). Thirteen neurons displayed heading and movement direction-dependent responses, and, of these 13, activity of 6 neurons increased during forward movement to the window or door side, while activity of the remaining 7 neurons increased during backward movement to the window or door side. Eighteen neurons showed movement direction-related responses regardless of heading direction. Furthermore, activity of some direction-related neurons increased only in a specific trajectory. These results suggested that the activity of these neurons reflects complex combinations of facing direction (landmarks), movement direction (optic flow/vestibular information), motor/proprioceptive information and the trajectory of the movement.